2017
DOI: 10.1242/jeb.155028
|View full text |Cite
|
Sign up to set email alerts
|

When less means more: dehydration improves innate immunity in rattlesnakes

Abstract: Immune function can vary based on availability of resources, and most studies of such influences have focused on the co-investment of energy into immune and other physiological functions. When energy resources are limited, trade-offs exist, which can compromise immunity for other functions. As with energy, water limitation can also alter various physiological processes, yet water has received little consideration for its possible role in modulating immune functions. We examined the relationship between immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…We did not detect any significant increases in agglutination, however. These results are consistent with findings of a positive relationship between hyperosmolality and innate immune performance in other squamates (Gila monsters; Moeller, Butler, & DeNardo, ; rattlesnakes; Brusch & DeNardo, ; Children's pythons; Brusch et al, ). As in those studies, we found that rehydration rapidly returned immune metrics to baseline values (Figure ), suggesting that the innate molecules responsible for the positive influence of dehydration on immune function rapidly disassociate or become ineffective upon rehydration.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We did not detect any significant increases in agglutination, however. These results are consistent with findings of a positive relationship between hyperosmolality and innate immune performance in other squamates (Gila monsters; Moeller, Butler, & DeNardo, ; rattlesnakes; Brusch & DeNardo, ; Children's pythons; Brusch et al, ). As in those studies, we found that rehydration rapidly returned immune metrics to baseline values (Figure ), suggesting that the innate molecules responsible for the positive influence of dehydration on immune function rapidly disassociate or become ineffective upon rehydration.…”
Section: Discussionsupporting
confidence: 88%
“…Comparing our data (pooled from our field and laboratory studies) with similarly pooled data from other experiments that used analogous methods on a sympatric species (Children's pythons; Brusch et al, ) and a xeric‐adapted species (western diamond‐backed rattlesnake; Brusch & DeNardo, ), reveal some interesting comparisons (Figure ). Water pythons have the smallest range of plasma osmolality of the three species (279–343 mOsm/kg), Children's pythons are intermediate (279–354 mOsm/kg), and rattlesnakes have the largest range (277–436 mOsm/kg).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations